2017
DOI: 10.1210/js.2017-00108
|View full text |Cite
|
Sign up to set email alerts
|

WISP1 Is a Marker of Systemic and Adipose Tissue Inflammation in Dysmetabolic Subjects With or Without Type 2 Diabetes

Abstract: Context:Wnt1-inducible signaling pathway protein 1 (WISP1) is a novel adipokine participating in adipose tissue (AT) dysfunction; so far, no data on WISP1 in diabetes are available.Objectives:To evaluate plasma WISP1 in subjects with type 2 diabetes (T2D) and its correlates linked to AT inflammation.Design and Participants:For this cross-sectional study, 97 consecutive dysmetabolic patients were recruited at the diabetes outpatient clinics of Sapienza University in Rome; 71 of them had T2D, with (n = 35) or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 32 publications
(44 reference statements)
8
50
0
Order By: Relevance
“…In vitro studies on primary hSkMCs as well as the mouse hepatocyte cell line AML12 showed that recombinant WISP1 directly impaired insulin action by inhibiting the Akt signalling pathway. The increased WISP1 expression in VAT of obese men is in line with previous reports from our group and others [13][14][15]26] suggesting that WISP1 expression is regulated by body weight. High-fat feeding in mice increased the expression of WISP1 in adipose tissue [13,27] while diet-induced weight loss in humans lowered WISP1 expression in adipose tissue [13].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In vitro studies on primary hSkMCs as well as the mouse hepatocyte cell line AML12 showed that recombinant WISP1 directly impaired insulin action by inhibiting the Akt signalling pathway. The increased WISP1 expression in VAT of obese men is in line with previous reports from our group and others [13][14][15]26] suggesting that WISP1 expression is regulated by body weight. High-fat feeding in mice increased the expression of WISP1 in adipose tissue [13,27] while diet-induced weight loss in humans lowered WISP1 expression in adipose tissue [13].…”
Section: Discussionsupporting
confidence: 92%
“…A study in women with gestational diabetes and insulin resistance showed increased circulating levels of WISP1 and identified BMI and insulin resistance as determinants of WISP1 levels [14]. Another very recently published study observed a direct relationship between circulating WISP1 levels and visceral adiposity and signs of insulin resistance, independently of glucose tolerance [15].…”
Section: Introductionmentioning
confidence: 98%
“…Two previous studies examined the association between circulating WISP1 and adult obesity status. One showed that WISP1 was sub-stantially overexpressed in visceral fat from obese subjects and reflected insulin resistance and inflammation of adipose tissue [18], whereas another study found that WISP1 levels increased in obese persons and were directly associated with adiposity, independent of glycemic status or insulin resistance [17]. In contrast, our findings demonstrated that prepregnancy overweight/obesity interacted with GDM to affect circulatory concentration of WISP1 (Figure 1(b)).…”
Section: Disease Markersmentioning
confidence: 51%
“…WISP1 is involved in a wide range of biological functions and pathological processes, such as cell growth, differentiation, and survival [13,14]. And overexpressed WISP1 has been observed in several diseases including GDM [15], hypertension [16], obesity [17,18], lung fibroblasts [19], and several types of cancer [20]. WISP1 is widely expressed in normal tissues, particularly in human adipose tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The proinflammatory potential of the adipokine was exhibited in vitro, when macrophages treated with WISP1 caused increased secretion of proinflammatory cytokines in a dose‐dependent fashion and polarized them to M1 phenotype . Serum concentration of the adipokine is elevated in obesity, irrespective of glycemia or insulin resistance status . This observation was reinforced in a different study, where WISP1 levels were found elevated in obese men irrespective of glycemic status compared with nonobese men .…”
Section: Adipokines and Therapies That Modulate Their Activitymentioning
confidence: 91%